1997
DOI: 10.1016/s0370-2693(97)00402-4
|View full text |Cite
|
Sign up to set email alerts
|

Scale factor duality and the energy condition inequalities

Abstract: We demonstrate, by a simple analysis, that cosmological line elements related by scale factor duality also exhibit a duality with respect to the conserva- Stringy cosmologies (for reviews, see [8], [9] ) have certain characteristic features apart from the symmetry of scale factor duality. Firstly, one does not need to bring in an ad-hoc scalar field to get the necessary inflationary phase. The dilaton field which arises as one of the massless excitations of the string world sheet serves the purpose. Moreover, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
4
2
0
Order By: Relevance
“…In particular, a duality is clearly seen for the ANEC along radial null geodesics. These facts substantiate the claim made earlier for black holes [18] and cosmologies [19] that there is a duality in the conservation/violation of the energy conditions for stringy spacetime geometries.…”
Section: Energy Conditionssupporting
confidence: 89%
See 1 more Smart Citation
“…In particular, a duality is clearly seen for the ANEC along radial null geodesics. These facts substantiate the claim made earlier for black holes [18] and cosmologies [19] that there is a duality in the conservation/violation of the energy conditions for stringy spacetime geometries.…”
Section: Energy Conditionssupporting
confidence: 89%
“…This fact was noted for the Einstein-scalar system in the Einstein frame by Roberts and there do exist recent verifications of this in the context of scalar field collapse through the numerical work of Choptuik and others [16] which indicate the existence of point-mass black holes (essentially naked singularities!). Finally, we demonstrate a reflection of string dualities in the conservation/violation of the local and global null energy condition-a fact which was noticed earlier for black holes and cosmologies in earlier papers by this author [18], [19].…”
Section: Introductionsupporting
confidence: 75%
“…Further, it can be shown that the Weak Energy Condition (WEC) is violated in this solution (Bose & Kar 1997). In fact this agrees with the recent result of Brustein & Madden (1997) and Kar (1996).…”
Section: Discussionsupporting
confidence: 93%
“…The peculiarity of the PBB inflation is that even classically the weak energy condition [5] is violated during that epoch when the equation are written in the form of the Einstein equations [6], while the strong energy condition is violated but the weak energy condition is respected classically in the case of the usual (potential energy dominated) inflation. This suggests that the behaviour of inhomogeneities in the PBB inflation is quite different from that in the usual inflation.…”
Section: Introductionmentioning
confidence: 99%